Listeria monocytogenes in horses in Iceland - Gudmundsdottir, K. B.; Svansson, V.; Gunnarsson, E.; Sigurdarson, S.; Aalbæk, B. (Veterinary Record, 2004)
Twenty isolates of Listeria monocytogenes associated with five confirmed and four suspected incidents oflisteriosis in horses in Iceland were characterised by serotyping, pulsed-field gel electrophoresis andribotyping. Semiquantitative estimates of the numbers of L monocytogenes were made on faeces fromhorses with clinical signs of listeriosis and on grass silage fed to them. Large numbers of L monocytogeneswere often found in the faeces of horses with severe signs of disease. The 20 isolates could be divided intosix genotypes, each incident involving only one genotype. One serovar 1/2a genotype was associated withthree confirmed incidents of listeriosis in 1991, 1993 and 1997. In one incident, the same genotype wasisolated from the organs of a horse with listeriosis and from the spoiled grass silage fed to it.